2019
DOI: 10.30812/matrik.v19i1.496
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Rasa Nasionalisme Siswa Melalui Game Base Learning

Abstract: The birth of Game Based Learning take a new prespective to learing method while using a Game for learning proccess. This is a good opportunity for lecturer and theacher to increas and update their learning instrument that can be used. Some studies about game founded the approach of through the medium of games of the match learning in a significant way capable of effecting the improve achievement , the motivation to study , and the level of satisfaction in the style of of students to study. This study focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Massachussets Insitute of Technology (MIT) berhasil membuktikan bahwa game sangat berguna untuk meningkatkan logika berpikir dan pemahaman dalam menyelesaikan masalah, proyek game tersebut yang dinamai Scratch. Game edukatif sebagai media pembelajaran yang dapat digunakan untuk meningkatkan hasil belajar siswa (Krisdiawan, 2018;Nama et al, 2019;Sabri et al, 2020;Vitianingsih, 2017;Wijaya et al, 2019). Dalam desain sebuah game edukasi juga dibutuhkan tahapan-tahapan perancangan seperti perancangan sebuah sistem informasi atau yang sering disebut dengan (SDLC) System Developmet Life Cycle.…”
Section: Abstrakunclassified
“…Massachussets Insitute of Technology (MIT) berhasil membuktikan bahwa game sangat berguna untuk meningkatkan logika berpikir dan pemahaman dalam menyelesaikan masalah, proyek game tersebut yang dinamai Scratch. Game edukatif sebagai media pembelajaran yang dapat digunakan untuk meningkatkan hasil belajar siswa (Krisdiawan, 2018;Nama et al, 2019;Sabri et al, 2020;Vitianingsih, 2017;Wijaya et al, 2019). Dalam desain sebuah game edukasi juga dibutuhkan tahapan-tahapan perancangan seperti perancangan sebuah sistem informasi atau yang sering disebut dengan (SDLC) System Developmet Life Cycle.…”
Section: Abstrakunclassified
“…Previous research was conducted by Wijaya et al in 2019 related to increasing student nationalism attitudes through game-based learning. The results showed that the learning process using game-based learning media can increase student enthusiasm for learning and also nationalism, considering that many students are more interested in cooperating and prioritizing common interests and prioritize personal interests (Wijaya et al, 2019). Further research conducted by Firdausi and Bashofi in 2020 related to movie media in learning Indonesian national history to increase the nationalism of IKIP Budi Utomo Malang students shows that the development of video-based multimedia learning media can be done even though the results are still not optimal, especially in image visualization, but students have high enthusiasm in following the learning process so that it can increase student nationalism (Firdausi & Bashofi, 2020).…”
Section: Introductionmentioning
confidence: 99%